Die Entstehung der Nacherbschaft im Bürgerlichen Gesetzbuch - Kampmann, Philipp Georg (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The modern German Nacherbschaft – a type of remainder – is alien both to many contemporary bodies of law and to classical Roman law. How is it that the otherwise conservative German Civil Code has here gone a decisive step further than the ius commune? This question leads into the history of late Pandectism and of the German codifications, which both found similar practical results through very different conceptual approaches; and its answer provides a contribution to the history of the doctrine of hereditary law.